An Oral Health Status and Treatment Needed in Relation to Dental Knowledge, Among a Group of Children Attending Preventive Department, College of Dentistry, University of Baghdad - Shahbaa Munther (College of Dentistry/ University of Baghdad, 2015)
Background: Oral health represents an important base for human well-being; the heath of the body begins from oral cavity. Great deal has been applied to increase knowledge in the field of oral health in order to develop appropriate preventive program. This study was conducted in order to estimate the percentage and severity of dental caries and gingivitis among children attending Preventive Department in Collage of Dentistry, University of Baghdad and to determine dental treatment need for those patients, further more to study the relation of these variables with dental knowledge. Materials and Methods: The study group consists of 163 children with an age ranged from 6 to 14 years, who attended the preventive clinic for the first time to be involved in preventive program. Plaque index and gingival index were applied for examination of dental plaque and gingivitis, dental caries and treatment need was recorded according to criteria described by WHO. Dental knowledge of each child was evaluated by ten questions prepared for this reason. Results: The results showed that caries-experience among permanent teeth represented by DS and DMFS were (3.22 ± 0.31 and 4.09 ± 0.35) respectively, while caries-experience among deciduouse teeth represented by ds and dmfs were (6.79 ± 0.61 and 9.03 ± 0.81) respectively. Analysis of variance (one way ANOVA test-) showed that caries experience among permanent teeth increased with age (P < 0.001), while caries-experience among deciduous teeth decreased with age (P ˂0.001). The majority of studied sample were in need for one surface filling (93%) followed by two or more surface filling (66%). High percentage of children involved in this study had mild accumulation of plaque and mild gingivitis (69.93% and 83.43%) respectively. Evaluation of dental knowledge among those children showed that 67% of them had good dental knowledge (scores ˃5), but weak correlations were recorded between good dental knowledge and caries experience for deciduous teeth(r=0.12, P > 0.05) and for permanent teeth (r=0.22, P 0.05). Conclusion: those children need further motivation and instructions to improve their dental knowledge and to improve their attitude to change their behavior towards further improvement of oral hygiene and oral health.